2020
DOI: 10.1007/s10067-020-05376-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential similarities of COVID-19 and autoimmune disease pathogenesis and therapeutic options: new insights approach

Abstract: Cytokine pathways and their signaling disorders can be the cause of onset and pathogenesis of many diseases such as autoimmune diseases and COVID-19 infection. Autoimmune patients may be at higher risk of developing infection due to the impaired immune responses, the use of immunosuppressive drugs, and damage to various organs. Increased secretion of inflammatory cytokines and intolerance of the patient's immune system to COVID-19 infection are the leading causes of hospitalization of these patients. The conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 168 publications
0
56
0
3
Order By: Relevance
“…In 2015, French citizens were among the populations with the lowest perception of vaccine safety globally, with 41•0% disagreeing that vaccines are safe. 4 Data from 2019 showed that the perception of vaccine safety varies considerably with nationality. In Denmark, 47•2% of the population strongly agreed that vaccines are safe, compared with only 29•8% of the population in the Netherlands and 29•7% of the French population.…”
Section: National Differences In Vaccine Hesitancy: a Concern For The External Validity Of Vaccine Studiesmentioning
confidence: 99%
“…In 2015, French citizens were among the populations with the lowest perception of vaccine safety globally, with 41•0% disagreeing that vaccines are safe. 4 Data from 2019 showed that the perception of vaccine safety varies considerably with nationality. In Denmark, 47•2% of the population strongly agreed that vaccines are safe, compared with only 29•8% of the population in the Netherlands and 29•7% of the French population.…”
Section: National Differences In Vaccine Hesitancy: a Concern For The External Validity Of Vaccine Studiesmentioning
confidence: 99%
“…As a consequence, this signaling stimulates immunity cells involved in chronic inflammatory processes that can lead to pulmonary degeneration, pulmonary fibrosis, loss of function (with impaired oxygenation, culminating in a state of delayed hypoxia), hypoxemia, and anoxia (in more severe conditions), ultimately causing death [15]. Patients who have cardiopulmonary or metabolic comorbidities (e.g., diabetes mellitus), autoimmune diseases, or who are undergoing any treatment that might compromise their immunity (e.g., chemotherapy, radiotherapy, or corticotherapy) have a higher risk of death [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research conducted on a mouse model of malaria infection found that myelolymphoid IL‐7 Ra + cKit‐hi progenitor was effectively produced in response to IFN‐γ. After this study, it can be stated that IFN‐γ signaling greatly contributes to the production of myeloid cells and reduction of parasitic infection (Belyaev et al, 2010; Najafi et al, 2020). In addition to these factors, mesenchymal stem cells (MSCs) may be a regulator of urgent myelopoiesis in inflammatory conditions.…”
Section: Interferonsmentioning
confidence: 98%
“…On the other hand, IL‐17 family members can lead to the production of inhibitory cytokines like transforming growth factor beta (TGF‐β), which is associated with the inhibition of progenitor growth (Matsuzaki et al, 2018; Mojsilović et al, 2015) (Figure 1). IL‐17 appears to activate the apoptosis process in progenitors by activating NF‐κB pathway to prevent their proliferation (Najafi et al, 2020). Several studies have examined the role of this cytokine in hematopoietic malignancies such as AML (Han et al, 2014) and CLL (Jain et al, 2012) as well as its function in angiogenesis (Wakita et al, 2010; Wróbel et al, 2003).…”
Section: Interleukin‐17mentioning
confidence: 99%